Sustainable Efficiency and Productivity Dynamics in Sugar Industry: A Data Envelopment Analysis and Malmquist Productivity Index Approach - Azizah, Alya Nur; Handayani, Wiwik (LPPM Universitas Jambi, 2026)
This study analyzes the technical efficiency and sustainable productivity dynamics of the Tjoekir Sugar Factory under PT Sinergi Gula Nusantara during the 2021–2025 period. The Indonesian sugar industry continues to face structural challenges, including low productivity, aging production assets, and increasing dependency on sugar imports, making operational efficiency a critical issue for industrial sustainability. This research employed a quantitative approach using the output-oriented Data Envelopment Analysis (DEA) CCR model to measure relative technical efficiency and the Malmquist Productivity Index (MPI) to evaluate changes in Total Factor Productivity (TFP) through efficiency change and technological change decomposition. The findings reveal that the factory achieved efficient frontier performance in 2023 and 2025, while inefficiencies in other periods were associated with input slack and operational instability. The MPI results indicate that productivity growth was primarily driven by technological change rather than managerial efficiency improvement, suggesting that asset optimization through maintenance and overhaul played a significant role in enhancing operational performance. Furthermore, the study demonstrates that improved efficiency contributes to sustainability objectives by reducing production losses, optimizing by-product utilization, and supporting Environmental, Social, and Governance (ESG) practices within the company’s operations. This research highlights the importance of integrating technological reliability, operational management, and sustainability principles to strengthen the long-term competitiveness and resilience of Indonesia’s sugar industry.